Penetapan Kadar Flavonoid dan Uji Aktivias Antioksidan Ekstrak Etanol Daun Ketapang (Terminalia catappa L.) dengan Metode ABTS: Determination of Flavonoid Levels and Antioxidant Activity Test of Ethanol Etract Ketapang Leaf (Terminalia catappa L.) Using ABTS Method - Wahyuni Ningsih; Anita Dwi Septiarini; Weri Veranita (UIMA Press, 2023)
Ketapang leaves (Terminalia catappa L.) is a plant that contains chemical compounds such as flavonoids, alkaloids, tannins, triterpenoids or steroids, resins, and saponins. This compound has potential as an antioxidant in absorbing and neutralizing free radicals. This study aims to determine the levels of flavonoid compounds, to determine whether the ethanol extract of ketapang leaves has antioxidant activity as expressed by the IC50 value and to determine the antioxidant power of the ethanol extract of ketapang leaves. The extract was prepared by maceration method using 96% ethanol. Determination of flavonoid levels and antioxidant activity was carried out using a UV-Vis spectrophotometer. Antioxidant activity based on the free radical scavenging ability of the compound ABTS was measured at a wavelength of 740 nm at 17 minutes. The results of determining the levels of flavonoids in the ethanol extract of ketapang leaves were 17,710 QE. Antioxidant activity is expressed in the value of 50% Inhibitory Concentration (IC50) with a yield of 23.531 ppm in ethanol extract. Ketapang leaf ethanol extract has a very strong antioxidant activity.